Filosofia geométrica: crítica à retórica e apropriação da geometria no pensamento de Thomas Hobbes - David Emanuel de Souza Coelho (2015)
This study aims to understand the role of geometry in the thought of Thomas Hobbes exposing its genesis from the criticism made by the philosopher about the Renaissance rhetoric. The Renaissance humanism was the prevailing intellectual form at the beginning of modernity and the english philosopher was formed within it. The Hobbesian criticism of rhetoric was not only a critique of rhetoric as stylistic figure, but a criticism of a form of knowledge and ontology. The goal of such criticism was the hobbesian aim for the establishment of a scientific way of knowing, based on the geometry. He wanted to unify natural and social knowledge in a geometric totality. The study, therefore, aims to show the ontological character of rhetoric, hobbesian criticism about the rhetoric and the subsequent structuring of the new hobbesian thought through geometry.